2016
DOI: 10.2147/jpr.s70481
|View full text |Cite
|
Sign up to set email alerts
|

Cytidine 5’-diphosphocholine administration prevents peripheral neuropathic pain after sciatic nerve crush injury in rats

Abstract: BackgroundCytidine 5′-diphosphocholine (citicoline) has been shown to have beneficial effects in central nervous system injury as well as in motoric functional recovery after peripheral nerve injury. This study aimed to examine the effect of citicoline on prevention of neuropathic pain in a rat model of sciatic nerve crush injury.MethodsForty experimental rats were divided into four groups. In three groups, the right sciatic nerves were crushed in the mid-thigh region, and a gelatin sponge moistened with 0.4 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 22 publications
0
12
0
1
Order By: Relevance
“…In the EPT test, the groups receiving citicoline had a significantly lower percentage of a motor deficit than in the control group: for 0.4 and 0.8 mL, respectively, 14.28% and 20.6% ( p = 0.00). Citicoline in this test was effective in alleviating neuropathic pain and reducing motor deficit [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the EPT test, the groups receiving citicoline had a significantly lower percentage of a motor deficit than in the control group: for 0.4 and 0.8 mL, respectively, 14.28% and 20.6% ( p = 0.00). Citicoline in this test was effective in alleviating neuropathic pain and reducing motor deficit [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that sciatic nerve crush induces chronic neuropathic pain, 25 28 and axon regeneration plays a pivotal role in the maintenance of neuropathic pain. 29 , 30 With the development of in vitro miRNAs synthesis and delivery technology, those small nucleotide sequences have been deemed as a promising approach for gene therapies.…”
Section: Discussionmentioning
confidence: 99%
“…SFI analysis did not show significant differences between the three groups. From this study, it can be concluded temporarily that citicoline has the potential to help the recovery of peripheral nerves through its mechanism to help regenerate axons [17].…”
Section: Pathology Of Painful Diabetic Polyneuropathy Evidence Of Citicoline Effectiveness On Peripheral Nerve Lesion and Their Suggestedmentioning
confidence: 82%